Marketing in a changing environment - Holloway, Robert J. (Wiley, 1973)
The organization of the volume in the following divisions indicates the general nature and major emphases of our approach to the study of marketing: The nature of marketing in a changing environment, marketing environment and buyer behavior, marketing management in a changing environment, ...